China's audit market competition and the competitive strategies of the international Big 4 audit firms - Qingquan Xin; Yu Liu; Yiheng Tang (China Journal of Accounting Studies (CJAS), 2023)
This study investigates the competitive strategies of the international Big 4 audit firms when faced with regional competition from the local Big 6 audit firms. We find that for the Big 4, competition reduces their audit fee premiums and forces them to recruit high-risk clients, while does not affect their audit quality. In further analyses, we find that competition led to greater changes for the Big 4 after the CICPA's proposal in 2007 and when the local Big 6 are in leading positions. We also find that the local Big 6 compromise on audit quality in addition to audit fee premiums and client criteria when faced with competition from small local audit firms. Overall, this study reveals the competitive strategies of the Big 4 under competitive pressure from the local Big 6, which suggests that local audit firms can compete with international audit firms for audit services by scale development.
Keywords: 650; Market competition; Big 4; audit fees; client risk; auditquality